Development prospects of international tourism in The Black Sea region - Parfinenko, Anatolij; Dubova, Daria (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2018)
The article highlights the strategic location of the Black Sea region as a distinct geographical and economic zone. The authors characterize natural recreational resources and tourism infrastructure as the major competitive advantage of the region for the development of tourism. The study analyzes the current socio-economic and political situation in the region, which is a factor in tourism development. The paper highlights the current state of development of cruise tourism in the Black Sea basin; designates the place and role of Ukraine and Odesa seaport in the development of cruise itineraries in the region. The authors come to the conclusion that cruise tourism is one of the most promising sectors of tourism in the Black Sea basin upon condition of maintaining competitive advantages and improving the socio-economic situation